Strategic Adaptations and Long-Term Organizational Change in Technology Companies Post-Pandemic: An Analysis of Remote Work Implementation and its Implications (المجلة الدولية للبحوث العلمية, 2024)
This research is investigating the impact of the remote work revolution intensified by the COVID-19 pandemic in the technology companies. The research is comprehensively evaluating that how remote work affects organizational operations, employee adaptability, productivity, and cost savings. It is aiming is for understanding the long-term sustainability of remote work practices and their effect on organizational flexibility and employee satisfaction. The research is employing a qualitative approach, integrating interviews, surveys, and empirical data analysis. It is focusing on the demographic and technological factors that influence work adaptability and the overall experience of remote work.The key findings of this research indicate that while remote work has increased productivity and reduced costs for many organizations but some challenges such as maintaining employee engagement and managing remote communication persist. Despite these challenges, the research is suggesting that remote work can be a sustainable practice if organizations tailor their strategies to address individual and organizational needs effectively.The study contributes to the academic and professional discourse on remote work especially in technology companies, and it is providing actionable insights for organizations to enhance their remote work policies and practices, ultimately it is aiming to optimize both employee well-being and organizational performance in a post-pandemic world.